John Gill Shorter correspondence - Shorter, John Gill, 1818-1872.
ALS (1862 April 4) from Shorter to Col. Tennent Lomax concerning military organization, recruiting, and location of camps in Alabama, the defense of Mobile, Ala., and Pensacola, Fla., and public support of the Civil War; and ALS (1862 May 2) from Shorter to F. W. Pickens, governor of South Carolina, relating to conscription, manufacture of arms and amunitions, Confederate finance, and Shorter's commitment to the Confederate cause.
Governor of Alabama and jurist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lomax, Tennent, -- 1820-1862 -- Correspondence; Pickens, F. W. -- 1805-1869 -- Correspondence; Confederate States of America. -- Army -- Recruiting, enlistment, etc; Military camps -- Alabama; Military weapons industry -- Southern States; Alabama -- History -- Civil War, 1861-1865.; Alabama -- Politics and government -- 1861-1865.; Florida -- History -- Civil War, 1861-1865.; Mobile (Ala.) -- History -- Civil War, 1861-1865.; Pensacola (Fla.) -- History -- Civil War, 1861-1865.; South Carolina -- Politics and government -- 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Finance; United States -- History -- Civil War, 1861-1865 -- Public opinion, Confederate; Governors -- Alabama; Jurists